2020
DOI: 10.3389/fmicb.2020.560488
|View full text |Cite
|
Sign up to set email alerts
|

Two Type VI Secretion Systems of Enterobacter cloacae Are Required for Bacterial Competition, Cell Adherence, and Intestinal Colonization

Abstract: Enterobacter cloacae has emerged as an opportunistic pathogen in healthcareassociated infections. Analysis of the genomic sequences of several E. cloacae strains revealed the presence of genes that code for expression of at least one type VI secretion system (T6SS). Here, we report that E. cloacae strain ATCC 13047 codes for two functional T6SS named T6SS-1 and T6SS-2. T6SS-1 and T6SS-2 were preferentially expressed in tryptic soy broth and tissue culture medium (DMEM), respectively. Mutants in T6SS-1-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 71 publications
0
28
0
Order By: Relevance
“…Briefly, Soria-Bustos and colleagues showed for E. cloacae strain ATCC 13047 that the T6SS-2 genes were highly expressed upon growth of the bacteria in Dulbecco's modified Eagle's medium (DMEM) while this was not the case in LB medium (the growth medium of our study). These authors also suggested that the T6SS-2 was implicated in biofilm formation and cell adherence and that it contributed to bacterial colonization of the mouse gut in vivo 41 . The finding on the system's functionality should be taken with caution, however, as Donato and colleagues showed that the T6SS-2 of E. cloacae strain ATCC 13047 was defective due to a large deletion and the insertion of an IS903 element, which led to the pseudogenization of several T6SS-2 genes (clpV2, vgrG3, PAAR, and tssF2) 42 .…”
Section: Resultsmentioning
confidence: 97%
“…Briefly, Soria-Bustos and colleagues showed for E. cloacae strain ATCC 13047 that the T6SS-2 genes were highly expressed upon growth of the bacteria in Dulbecco's modified Eagle's medium (DMEM) while this was not the case in LB medium (the growth medium of our study). These authors also suggested that the T6SS-2 was implicated in biofilm formation and cell adherence and that it contributed to bacterial colonization of the mouse gut in vivo 41 . The finding on the system's functionality should be taken with caution, however, as Donato and colleagues showed that the T6SS-2 of E. cloacae strain ATCC 13047 was defective due to a large deletion and the insertion of an IS903 element, which led to the pseudogenization of several T6SS-2 genes (clpV2, vgrG3, PAAR, and tssF2) 42 .…”
Section: Resultsmentioning
confidence: 97%
“…6). It has been previously shown that a clpV2 knockout strain of Enterobacter cloacae exhibited a significant decrease in biofilm formation (50), that a clpV3 deletion resulted in smaller P. aeruginosa biofilms (51), and that a ppkA deletion mutant of P. aeruginosa has a biofilm-formation defect (52). In addition, the expression of the hemolysin-coregulated protein Hcp3, an important effector protein of the type-VI secretion system, is increased in biofilm-forming compared to non-biofilm-forming clinical isolates of P. aeruginosa and is associated with more severe symptoms such as longer hospitalization (53).…”
Section: Discussionmentioning
confidence: 99%
“…The aroX and NRPS operons encode the proteins involved in the biosynthesis of TV and are clustered in a PAI that is only present in the K. oxytoca toxigenic strains ( Schneditz et al, 2014 ; Dornisch et al, 2017 ). In this study, we analyzed the expression of aroX and NRPS operons in strains growing in various culture media since previous work has determined that nutritional components are environmental stimuli that trigger a differential expression of genes related to bacterial virulence ( Blair et al, 2013 ; De la Cruz et al, 2017 ; Han et al, 2017 ; Ares et al, 2019 ; Soria-Bustos et al, 2020 ; Jiang et al, 2021 ). Our results showed that TLB culture medium significantly enhanced the expression of the aroX and NRPS operons, in agreement with a previous report in which the production of TV significantly increased in the toxigenic strain K. oxytoca MH43-1 when the bacterium was grown in TLB as compared with TSB and LB ( Tse et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%